2016
DOI: 10.1080/08869634.2016.1271502
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular position influence on pilots’ postural balance analyzed under dynamic conditions

Abstract: The findings of this study seem to suggest that the composite parameter of the SOT is not sensitive in analyzing the influence of the stomatognathic system on the postural balance of civilian and military pilots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
1
3
0
1
Order By: Relevance
“…In addition, an interaction between dental occlusion and external disturbances on the balancing ability has been recently described using dynamic posturography (EquiTest system) . Baldini et al evaluated the influence of the mandibular position on postural stability also using the EquiTest posturography with the addition of performing a sensory organisation test (SOT) . However, in contrast to the results reported by Hosoda et al, others found that postural balance was not influenced by the occlusal condition.…”
Section: The Importance Of the External Environmental On The Relationsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, an interaction between dental occlusion and external disturbances on the balancing ability has been recently described using dynamic posturography (EquiTest system) . Baldini et al evaluated the influence of the mandibular position on postural stability also using the EquiTest posturography with the addition of performing a sensory organisation test (SOT) . However, in contrast to the results reported by Hosoda et al, others found that postural balance was not influenced by the occlusal condition.…”
Section: The Importance Of the External Environmental On The Relationsupporting
confidence: 80%
“…However, in contrast to the results reported by Hosoda et al, others found that postural balance was not influenced by the occlusal condition. These authors concluded SOT probably not to be sensitive in analysing the influence of the stomatognathic system on the postural balance . In this regard, recent research suggested that altering dental occlusion by wearing a mandibular orthopaedic repositioning appliance (MORA) could induce some fluctuation in the dynamic postural attitude measured with a Fukuda‐Unterberg experimental stepping test …”
Section: The Importance Of the External Environmental On The Relationmentioning
confidence: 99%
“…For example “Dental Barotrauma” frequently reported during the WWII period, that deals with fracturing of restorations during high-altitude flying 6 or barodontalgia, which affects 11% of military aircrews at a rate of 5 episodes/1000 flights 7 . Furthermore, probably because of the physical and psychological stresses related with their employment, military pilots are frequently affected by bruxism, disorder characterized by grinding and clenching of the teeth occurring without a functional purpose 8–10 . This was clearly showed in a study published by Lurie et al .…”
Section: Introductionmentioning
confidence: 99%
“…Essa posição leva à hiperextensão da cabeça sobre o pescoço, quando o paciente corrige para as necessidades visuais, flexão da cervical baixa sobre o tórax e posteriorização da mandíbula. Esses fatores podem levar à dor e à disfunção na cabeça e pescoço (BALDINI et al, 2016).…”
Section: Discussionunclassified